ANALISIS PENGARUH BRAND IMAGE, BRAND RESONANCE, DAN BRAND TRUST TERHADAP BRAND LOYALTY PRODUK SEPATU CONVERSE PADA MAHASISWA DI SOLORAYA - Iva Nur Fadillah; Moecammad Nasir (Value : Jurnal Manajemen dan Akuntansi, 2023)
The business world in the fashion sector is currently developing rapidly, resulting in increasingly fierce competition. As customers are getting smarter and more demanding, companies must come up with fresh ideas and innovate. Fashion today is increasingly modern, so it makes people try to look more up to date. Especially among students who are very concerned about fashion to look cooler and tidier. The purpose of this study is to analyse the effect of brand image, brand resonance and brand trust on brand loyalty in Converse Shoe products for students in Soloraya. The research method is explanatory research. This research method is quantitative. The population of this study were students in Soloraya who bought and wore Converse brand shoes and the sample of this study were 202 respondents. Non-probability sampling was used as a sampling technique. The data analysis technique in this study used Patrial Least Square (PLS) with the help of SmartPLS software. The results of this study brand image variables have a positive and significant effect on brand loyalty. Brand resonance variables have a positive and significant effect on brand loyalty. The brand trust variable has a positive and significant effect on brand loyalty in Converse Shoes. Keywords: Brand Image; Brand Resonance; Shoes